2017
DOI: 10.1038/srep41499
|View full text |Cite
|
Sign up to set email alerts
|

CD133+ cancer stem cells promoted by VEGF accelerate the recurrence of hepatocellular carcinoma

Abstract: The role of cancer stem cells (CSCs) in inducing the recurrence of hepatocellular carcinoma (HCC) after radiofrequency ablation (RFA) remains unclear. Here, we found that a dramatic increase in plasma vascular endothelial growth factor (VEGF) and an induction of local CD133+ CSCs are associated with early HCC recurrence, suggesting that VEGF expression and tumour stemness contribute to the relapse. In vitro studies demonstrated that VEGF, via activation of VEGFR2, increased the number of CD133+ CSCs and enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…Here, we further measured the IC 50 values of sorafenib in four HCC cell lines, including Hep3B, Huh7, pHCC1, and pHCC2. pHCC2 was the other human primary HCC cell lines established by us previously . As shown in Figure A, the IC 50 value of pHCC2 was up to 15 μM, which was more than the value of sorafenib concentration (10 μM) for inducing SR; the IC 50 values of Hep3B, Huh7, and pHCC1 were less than 5 μM.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Here, we further measured the IC 50 values of sorafenib in four HCC cell lines, including Hep3B, Huh7, pHCC1, and pHCC2. pHCC2 was the other human primary HCC cell lines established by us previously . As shown in Figure A, the IC 50 value of pHCC2 was up to 15 μM, which was more than the value of sorafenib concentration (10 μM) for inducing SR; the IC 50 values of Hep3B, Huh7, and pHCC1 were less than 5 μM.…”
Section: Resultsmentioning
confidence: 88%
“…Hep3B, Huh7, and a primary HCC cell line (pHCC1) established previously by Liu et al were used to produce three SR human HCC cell lines. MTT assay determined that 10 μM sorafenib treatment significantly reduced the viability of three wild‐type cell lines, but failed to reduce the viability of three SR cell lines (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recurrence rate of patients with a high CD133 expression is higher than that of a low CD133 expression (Song et al, 2008). The process of CD133 + CSCs promoting the recurrence of HCC is closely associated with VEGF (Liu et al, 2017a). Other studies have shown that CD44 expressions in nontumor tissues may predict HCC recurrence (Tovuu et al, 2013).…”
Section: Cscs Affect Hcc Recurrencementioning
confidence: 98%
“…Cancer stem cells (CSCs) represent a subpopulation of cancer cells with innate resistance to radio and chemotherapies and are vital for tumor progression and recurrence after therapy [ 6 , 7 ]. Accumulating evidences suggest that a small subset of HCC possess these stem like properties and thus are important targets for therapeutic interventions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%